Modified Hodge Test For Detection Of Carbapenemase In Clinical Isolates Of Pseudomonas Aeruginosa. - Dr.Shweta Sao, Mihir Pattanayak, Mrs.Jyoti Aswani Dr. Ramnesh Murthy (International Journal of Scientific Research and Management (IJSRM), 2015)
The clover leaf test or modified Hodge test (MHT) has been extensively used as a general phenotypic method for the detection of carbapenemase activity, and it is the only method of carbapenemase detection so far recommended by the CLSI. The test is sensitive for the detection of a carbapenemase mediated mechanism of resistance to carbapenems, but does not provide information on the type of carbapenemase involved.